Collagen‐rich deposit formation in the sciatic nerve after injury and surgical repair: A study of collagen‐producing cells in a rabbit model. Issue 10 (15th August 2020) - Fertala, Jolanta; Rivlin, Michael; Wang, Mark L.; Beredjiklian, Pedro K.; Steplewski, Andrzej; Fertala, Andrzej
Abstract: Introduction: Posttraumatic scarring of peripheral nerves produces unwanted adhesions that block axonal growth. In the context of surgical nerve repair, the organization of the scar tissue adjacent to conduits used to span the gap between the stumps of transected nerves is poorly understood. The goal of this study was to elucidate the patterns of distribution of collagen‐rich scar tissue and analyze the spatial organization of cells that produce fibrotic deposits around and within the conduit's lumen. Methods: Employing a rabbit model of sciatic nerve transection injury, we studied the formation of collagen‐rich scar tissue both inside and outside conduits used to bridge the injury sites. Utilizing quantitative immunohistology and Fourier‐transform infrared spectroscopy methods, we measured cellular and structural elements present in the extraneural and the intraneural scar of the proximal and distal nerve fragments. Results: Analysis of cells producing collagen‐rich deposits revealed that alpha‐smooth muscle actin‐positive myofibroblasts were only present in the margins of the stumps. In contrast, heat shock protein 47‐positive fibroblasts actively producing collagenous proteins were abundant within the entire scar tissue. The most prominent site of transected sciatic nerves with the highest number of cells actively producing collagen‐rich scar was the proximal stump. Conclusion: Our findings suggest the proximal region of the injury site plays a prominent role in pro‐fibrotic processes associated with the formation of collagen‐rich deposits. Moreover, they show that the role of canonical myofibroblasts in peripheral nerve regeneration is limited to wound contracture and that a distinct population of fibroblastic cells produce the collagenous proteins that form scar tissue. As scarring after nerve injury remains a clinical problem with poor outcomes due to incomplete nerve recovery, further elucidation of the cellular and spatial aspects of neural fibrosis will lead to more targeted treatments in the clinical setting. Abstract : In this study, we analyzed collagen‐rich deposits formed in response to the injury of the sciatic nerve. Utilizing microscopic and spectroscopic techniques, we determined the distribution and architecture of fibrotic deposits formed in the proximal and the distal stumps of the injured nerve.